(3eUHGM GdCfGe aj TQM TQGjY GdESdGes - (3GdHOjQj, GdfLaj, LYaQ Hf CMeO Hf Sja, J (B1369 (3g`s
(3ChdgG (B:s
(3HSe Gddg (B.. (3bhdg NGJeI JTJed Ydi aUdjf GdChd aj cJGH bGVj (B... (3GfgGA Mce GdMGce Edi GdBNQ CeG HGdcJGH Ch Gdbhd Ch GdTgGOI CeG GdcJGHI adG YHQI HgG dG ecGf GdJTHjg hCeG Gdbhd (B...s
(3BNQgG (B:s
.. (3hbGYOI GdOYhi HdG eYGQV hcd EdMGbg HGdOYhi GdeTJQcI deLghd fHfj GKfjf aUGYOG hdcf jJYjf dCMOgeG (B... (3hGdMeO ddg QH GdYGdejfs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B2\ 121s
(3GdPQjYI (B21\4132s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis